2013
DOI: 10.1016/j.surg.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and therapeutic implications of Sprouty2 feedback dysregulation in BRAF V600E-mutation-positive papillary thyroid cancer

Abstract: Background The BRAF V600E (BRAF+) mutation activates the MAPK/ERK pathway and may confer an aggressive phenotype in papillary thyroid cancer (PTC). However, clinically BRAF+PTC behavior varies from indolent to aggressive. SPRY2 is a negative feedback regulator of the MAPK/ERK pathway. We hypothesize that the level of SPRY2 expression contributes to MAPK/ERK pathway output and accounts for BRAF+ clinical heterogeneity. Methods A tissue microarray with BRAF+PTCs was constructed and analyzed for SPRY2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In particular, in papillary thyroid cancer, the presence of the BRAF V600E mutation appears to be associated with a markedly worse prognosis, regardless of initial stage, 38 especially in the presence of other molecular cellular abnormalities. 39 In clinical practice, the results of the present study imply that the empirically derived TNM system is a safe choice for any centre that does not wish to go through the extensive and difficult process of deriving and validating a prognostic system for their own patient population. This is in spite of several groups who developed their own prognostic system and who reported that their particular system was superior in their specific patient population.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In particular, in papillary thyroid cancer, the presence of the BRAF V600E mutation appears to be associated with a markedly worse prognosis, regardless of initial stage, 38 especially in the presence of other molecular cellular abnormalities. 39 In clinical practice, the results of the present study imply that the empirically derived TNM system is a safe choice for any centre that does not wish to go through the extensive and difficult process of deriving and validating a prognostic system for their own patient population. This is in spite of several groups who developed their own prognostic system and who reported that their particular system was superior in their specific patient population.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, in the future, it is not unlikely that current staging systems such as the TNM system, which are based on traditional clinical measures of extent of disease as an indicator for tumour aggressiveness and prognosis, will be superseded by novel or amended with classifications based on molecular markers. In particular, in papillary thyroid cancer, the presence of the BRAF V600E mutation appears to be associated with a markedly worse prognosis, regardless of initial stage, especially in the presence of other molecular cellular abnormalities …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed out the significant role of sprouty2, a substrate of Mnk1, during multiple diseases or physiological process such as human mesenchymal stem cell differentiation, 17 papillary thyroid cancer, 18 and prostate cancer progression 19 by regulating ERK signaling pathway. ERK1/2 is one of the most important signaling that could provide new treatment strategies for cardiac hypertrophy and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with PTC who have a serine/threonine-protein kinase B-raf (BRAF) Val600Glu mutation differ with regard to the presence of lymph node metastases, depending on the expression level of protein sprouty homologue 2 (SPRY2), a negative regulator of the mitogen-activated protein kinase (MAPK, also known as ERK) pathway; those with a dysregulated MAPK pathway develop lymph node metastases, whereas those with an intact MAPK pathway do not. 38 Once such mechanisms have been identified and individualized therapy adjusted accordingly, it is conceivable that pro cedures such as prophylactic central compartment dissec tion might yield a prognostic advantage. By contrast, there is little discussion about whether surgical removal of lateral neck lymph nodes should only be performed when there is evidence or strong suspicion of the presence of loco regional metastases.…”
Section: Extent Of Surgerymentioning
confidence: 99%
“…131 Other cellular pathways and targets, such as protein sprouty homologue 2, need to be dysregulated in addition to the aforementioned mutations in order for a DTC to show a more aggressive clinical behaviour. 38 In this regard, further studies linking molecu lar testing and tumour markers with long-term patient outcomes are needed. The collection of large numbers of tumour samples in tissue banks would facilitate such correlative studies.…”
Section: Individualized Molecular Treatmentsmentioning
confidence: 99%